The Relationship between Acute: Chronic Workload Ratio of High-Speed Running and Hamstring Injuries in Professional Footballers - Thomas Gee (International Universities Strength and Conditioning Association, 2022)
Hamstring strain injuries are common within professional footballers with high-speed running (HSR) being known to increase the likelihood of sustaining a hamstring injury. This study aimed to assess the acute: chronic workload ratio (ACWR) of HSR that preceded hamstring injuries in professional footballers. Global positioning system (GPS)-derived HSR distances and weekly ACWR were obtained from 18 footballers from one English Football League (EFL) club during the 2018-2019 season. Hamstring injuries were documented by the club's medical team and the ACWR data of the four weeks preceding each hamstring injury were analysed. The mean ACWR of injured players was calculated for each season along with the ACWR of the squad. Ten hamstring injuries were recorded in total, across eight of the 18 players (44%). The most common site of injury was the medial part of the hamstring (70%). At the time of injury the mean ACWR for injured players was 0.90, while the squad mean ACWR for the season was 1.04. In conclusion, this study evidenced a high prevalence of non-contact hamstring injuries over a competitive season within an EFL club. The majority of hamstring injuries occurred when the mean ACWR was below the squad mean ACWR for the season. The loading pattern of 'moderate to high' followed by 'low to moderate' ACWR was commonly observed in the four weeks prior to injury.